Estimating characteristics of the foreign-born by legal status an evaluation of data and methods - Swanson, David A. (SpringerBriefs in population studies, 2011)
This brief represents a comprehensive review of methods for estimating characteristics of the foreign-born population in the United States, specifically oriented toward characteristics by legal status. A variety of methods have been proffered over the past many decades, in a large variety of venues; this work brings them together, attempts to impart some order on the definition of legal status, and describes strengths and deficiencies both in methods and in data. The authors have a combined 50 years of experience in both demographic and statistical methodology.